1992
DOI: 10.1007/bf00028889
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the pea metallothionein-like gene PsMT A in Escherichia coli and Arabidopsis thaliana and analysis of trace metal ion accumulation: Implications for PsMT A function

Abstract: The PsMTA gene from pea (Pisum sativum) shares similarity with metallothionein (MT) genes and related sequences have also been isolated from a number of other higher-plant species. The proteins encoded by these genes have not yet been purified from plants and their functions remain unclear although, by analogy to MT, roles in the metabolism and detoxification of metal ions have been proposed. By contrast, correlation between transcript abundance and Fe availability has led to an alternative proposal that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(79 citation statements)
references
References 37 publications
6
68
0
2
Order By: Relevance
“…Here we have demonstrated that six Arabidopsis MTs, including representatives of all four types of plant MTs, can impart metal tolerance when expressed in S. cerevisiae. Although the metal-binding capacity of some plant MTs has been previously demonstrated (Tommey et al, 1991;Evans et al, 1992;Murphy et al, 1997), this is the first report, to our knowledge, to compare all four types of MTs from a single plant species. Our results suggest that all MT isoforms are able to bind Cu ions in vivo.…”
Section: Discussion Arabidopsis Mts Can Impart Metal Tolerance In Vivomentioning
confidence: 76%
“…Here we have demonstrated that six Arabidopsis MTs, including representatives of all four types of plant MTs, can impart metal tolerance when expressed in S. cerevisiae. Although the metal-binding capacity of some plant MTs has been previously demonstrated (Tommey et al, 1991;Evans et al, 1992;Murphy et al, 1997), this is the first report, to our knowledge, to compare all four types of MTs from a single plant species. Our results suggest that all MT isoforms are able to bind Cu ions in vivo.…”
Section: Discussion Arabidopsis Mts Can Impart Metal Tolerance In Vivomentioning
confidence: 76%
“…Various MT genes Ð mouse MTI, human MTIA (alpha domain), human MTII, Chinese hamster MTII, yeast CUP1, pea PsMTA Ð have been transferred to Nicotiana sp., Brassica sp. or A. thaliana (Lefebvre et al, 1987;Maiti et al, 1988Maiti et al, , 1989Maiti et al, , 1991Misra and Gedamu, 1989;Evans et al, 1992;Yeargan et al, 1992;Brandle et al, 1993;Pan et al, 1993Pan et al, , 1994aElmayan and Tepfer, 1994;Hattori et al, 1994;Hasegawa et al, 1997). As a result, varying degrees of constitutively enhanced Cd tolerance have been achieved, being maximally 20-fold compared with the control.…”
Section: Mts and CD Tolerancementioning
confidence: 99%
“…Only one study has been reported on a transgenic plant generated with MT of plant origin. When pea (Pisum sativum) MT-like gene PsMTA was expressed in A. thaliana, more Cu (several-fold in some plants) accumulated in the roots of transformed than of control plants (Evans et al, 1992). We have recently isolated an MT gene from metal-tolerant Silene vulgaris and transferred it into several metal-sensitive yeasts (Tervahauta et al, unpublished).…”
Section: Mts and CD Tolerancementioning
confidence: 99%
“…However, in neither case was the identity of the proteins convincingly demonstrated. Plant MT cDNAs have been shown to complement cup-copper-sensitive yeast mutants, and the proteins could be purified after overexpression in Escherichia coli (Evans et al, 1992;Robinson et al, 1993;Zhou and Goldsbrough, 1994). However, efforts to purify the proteins from plant tissues, even when ectopically expressed, have been unsuccessful.…”
mentioning
confidence: 99%